1993
DOI: 10.1002/1097-0142(19930101)71:1<9::aid-cncr2820710104>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the treatment of advanced colorectal cancer

Abstract: The treatment of advanced colorectal cancer has improved in recent years. Prospective randomized trials comparing innovative therapies with the “standard” bolus dose of 5‐fluorouracil (5‐FU) found increased response rates after biochemical modification of the drug, infusion administration of 5‐FU, and direct intrahepatic arterial infusion. Although the impact on survival of these techniques has been minimal, it is possible that these innovative approaches provide an incremental survival advantage for certain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 45 publications
2
16
0
1
Order By: Relevance
“…However, the local effectiveness based on the rate of local recurrences was higher in patients with HCC vs the patients with metastases, in HCC local tumour control was 70% and in CRLM only 26%. The response in CRLM is comparable with these after systemic chemotherapy which mainly remains below 30% (Kemeny et al, 1993). For the HCC our results are comparable to these after chemoembolization or hepatic arterial infusion, a response of 30 -60% after TACE (Takayasu et al, 1989;GTCH 1995;Colella et al, 1998) and 40 -50% after HAI (Carr, 1996;Patt et al, 1997) is reported.…”
Section: Discussionsupporting
confidence: 81%
“…However, the local effectiveness based on the rate of local recurrences was higher in patients with HCC vs the patients with metastases, in HCC local tumour control was 70% and in CRLM only 26%. The response in CRLM is comparable with these after systemic chemotherapy which mainly remains below 30% (Kemeny et al, 1993). For the HCC our results are comparable to these after chemoembolization or hepatic arterial infusion, a response of 30 -60% after TACE (Takayasu et al, 1989;GTCH 1995;Colella et al, 1998) and 40 -50% after HAI (Carr, 1996;Patt et al, 1997) is reported.…”
Section: Discussionsupporting
confidence: 81%
“…The above results indicate that the therapy after recurrence contributed to prolonging life. In this connection, the following situations can be pointed out: good prognosis after resection for recurrences, which has recently begun to achieve positive results [25,26,27,28,29,30,31,32] and an improvement in chemotherapy, including loco-regional chemotherapy, using liver arterial infusion for progressive recurrent cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Despite overall 5-year survival rates of only 25 to 40%, surgical resection remains the treatment of choice for appropriately selected patients (2,3). The most common therapeutic modality used in patients presenting with colorectal hepatic metastases is systemic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%